2020
DOI: 10.13170/depik.9.3.15094
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi dan status guild komunitas ikan di Waduk Sempor Jawa Tengah

Abstract: Abstract.The functional community is described depends on the function of species in utilization food (guild). The utilization of food is a process of energy transfers in the food chain and it is represented in the pyramid of numbers. The objective of this research was to analyze the structure community of fish and the guild compositions in Sempor Reservoir. This research applied a survey with purposive random sampling technique with four station in Sempor Reservoir. Sampling at each site was taken 4 replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The reservoir is the essential habitat for fish species, including snakehead fish, and the land use activities can affect the abundance of snakehead fish. A previous study [9] reported that the snakehead fish catch in Sempor Reservoir is as low as 0,68% of 14 species. This low abundance is due to the disappearing habitat for spawning and rearing, diminished water quality, and water fluctuation [10].…”
Section: Introductionmentioning
confidence: 92%
“…The reservoir is the essential habitat for fish species, including snakehead fish, and the land use activities can affect the abundance of snakehead fish. A previous study [9] reported that the snakehead fish catch in Sempor Reservoir is as low as 0,68% of 14 species. This low abundance is due to the disappearing habitat for spawning and rearing, diminished water quality, and water fluctuation [10].…”
Section: Introductionmentioning
confidence: 92%